Clinical and epidemiological analysis of intestinal infections in a children's infectious diseases hospital, experience in using the PEWS scale - A. Y. Dyagileva; O. N. Solodovnikova; S. K. Pylaeva; K. A. Kiseleva; A. A. Erovichenkov; D. V. Troshchansky; I. N. Tyurin; D. N. Protsenko; O. V. Shamsheva (LLC "Diagnostics and Vaccines", 2024)
Purpose of the work: to conduct a clinical-epidemiological analysis of intestinal infections in a pediatric infectious diseases hospital and the effectiveness of the PEWS scale.Materials and methods: a retrospective study was conducted at the Moscow City Clinical Hospital «Communarka» and City Clinical Hospital No. 1 in the pediatric infectious disease departments from June 1, 2023, to August 31, 2023. Laboratory, clinical, and anamnestic data were obtained from the medical information system «EMIAS» and the laboratory information system (LIS) «ALISA». The study analyzed 838 medical records of children with acute respiratory infections.Results: when conducting a statistical analysis of indicators in two groups (group 1 - PEWS ≥ 3 points, recorded at least once during the entire period of hospitalization, group 2 - PEWS from 1 to 2 points, recorded at least once during hospitalization period) no significant differences were observed in terms of etiology, age, day of illness, blood test results, and length of hospital stay. All patients had a moderate form of acute respiratory infection, however, patients with PEWS ≥ 3 points required increased attention from medical staff and had a higher risk of deterioration without additional medical intervention, with the most significant risk in predicting deterioration being related to changes in the cardiovascular system. All children were discharged home in satisfactory condition with PEWS = 0.Conclusion: In our conducted research, for the first time in the Russian Federation, the experience of using the PEWS scale in pediatric practice for patients with gastrointestinal infections was applied with the aim of early detection of the risk of clinical deterioration. It can be assumed that the most significant risk in predicting deterioration in the condition of a child with acute gastrointestinal infection, as well as with acute respiratory infection, is predominantly due to disturbances in the cardiovascular system.